Are Adjustment Costs for Labor Asymmetric? An Econometric Test on Panel Data for Italy - Jaramillo, Fidel; Schiantarelli, Fabio; Sembenelli, Alessandro (The Review of Economics and Statistics, 1993)
Fidel Jaramillo, Fabio Schiantarelli, Alessandro Sembenelli, Are Adjustment Costs for Labor Asymmetric? An Econometric Test on Panel Data for Italy, The Review of Economics and Statistics, Vol. 75, No. 4 (Nov., 1993), pp. 640-648